(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to know the effect of a teaching strategy according to the (Double Diamond) model on mathematical reasoning The Second intermediate Grade students, and identified the mathematics teachers of the second intermediate, The research sample consisted of (83) students from the second intermediate grade at the Martyr Ali Hassan Al-Saadi Middle School for Boys, affiliated with the Directorate of Education of Baghdad / Al-Rusafa 3rd, for the academic year (2023-2024), the first course, It was chosen intentionally to implement the experiment and contained (6) groups, two of which were chosen randomly (by lottery) with (42) students for the experimental group and (41) students for the control group. The two research groups (experimental and control) were rewarded in variables: chronological age in months, Previous mathematics achievement, prior mathematical knowledge, and mathematical reasoning, The researcher prepared a mathematical reasoning test consisting of (20) items between objective (multiple choice) and essay. The validity and reliability of the test was verified. The results showed that the experimental group students who were taught using the Double Diamond model outperformed the mathematical reasoning test significantly compared to the control group students who were taught using the traditional (usual) method.